(untitled) (Fiep Bulletin - online, 2015)
The aim of study was observe the levels of quality of life(QOL) on elderly group. The amostral group live in Araruama RJ (BRASIL) (n-17) who had muscular diseases and ostheoartrits that reduce quality of life levels. Were used WHOQOL-100 to measure QOL levels before and after five sessions of shiatsutherapy. Statistic used: average, standard deviation, standard mistake, Curtose and Asymmetry, percentual variation Wilcoxon test. Results: dom1 14,53, dom2 14,70; dom3 13,56; dom4 13,50; dom5 13,06; dom6 16,89. It were possible observe significance difference p<0,05.